Panobinostat plus bortezomib and dexamethasone in previously treated multiple myeloma: Outcomes by prior treatment - Richardson, P.G.; Hungria, V.T.M.; Yoon, S.-S.; Beksac, M.; Dimopoulos, M.A.; Elghandour, A.; Jedrzejczak, W.W.; Guenther, A.; Na Nakorn, T.; Siritanaratkul, N.; Schlossman, R.L.; Hou, J.; et al. (Blood, 2016)
Panobinostat is a potent pan-deacetylase inhibitor that affects the growth and survival of multiple myeloma (MM) cells through alteration of epigenetic mechanisms and protein metabolism. Panobinostat plus bortezomib and dexamethasone (PAN-BTZ-Dex) led to a significant increase in progression-free survival (PFS) vs placebo plus bortezomib and dexamethasone (Pbo-BTZ-Dex) in patients with relapsed or relapsed and refractoryMMin the phase 3PANORAMA1 trial. This subgroup analysis evaluated outcomes in patients in the PANORAMA 1 trial based on prior treatment: A prior immunomodulatory drug (IMiD; n 5 485), prior bortezomib plus an IMiD (n 5 193), and ≥2 prior regimens including bortezomib and an IMiD (n5147). Median PFS with PAN-BTZ-Dex vs Pbo-BTZ-Dex across subgroups was as follows: prior IMiD (12.3 vs 7.4 months; hazard ratio [HR], 0.54; 95% confidence interval [CI], 0.43-0.68), prior bortezomib plus IMiD (10.6 vs 5.8 months; HR, 0.52;95%CI, 0.36-0.76),and ≥2 prior regimens including bortezomib and an IMiD (12.5 vs 4.7 months; HR, 0.47; 95% CI, 0.31-0.72). Common grade 3/4 adverse events and laboratory abnormalities in patients who received PAN-BTZ-Dex across the prior treatment groups included thrombocytopenia, lymphopenia, neutropenia, diarrhea, and asthenia/ fatigue. Incidence of on-treatment deaths among patients who received prior bortezomib and an IMiD (regardless of number of prior regimens) was similar between treatment arms. This analysis demonstrated a clear PFS benefit of 7.8 months with PAN-BTZ-Dex among patients who received ‡2 prior regimens including bortezomib and an IMiD, a population with limited treatment options and poorer prognosis. This trial was registered at www.clinicaltrials.gov as #NCT01023308. © 2016 by The American Society of Hematology.